Optimized conditions for grafting reaction of poly (methyl methacrylate) onto talc filler - Abu Bakar, A. (Faculty of Chemical and Natural Resources Engineering,Universiti Teknologi Malaysia, 2008)

(untitled)
In this study, poly(methyl methacrylate) (PMMA) grafted onto talc was produced using free radical polymerization. Hydrogen peroxide (H202) and ferrous ions (Fe2+) were used as a redox initiator/co-catalyst system. Grafting copolymerization was carried out under nitrogen atmospheric since it is known that oxygen presence will terminate the free radical mechanism. The PMMA homopolymer formed during the reaction was removed from the graft copolymer by Soxhlet extraction using acetone. The grafting percentage and grafting efficiency were systematically investigated. The parameter variables; reaction time, reaction temperature and concentration of ammonium ferrous sulfate directly influenced the graftina percentage. The percent grafting increased to a certain value in each variable. The optimmll conditions for reaction period, reaction temperature and initiator concentrations were 60 minutes, 52°C and 4.87 x 10-3 mol, respectively. Fourier-transform infrared spectroscopy was used to observe the difference between ungrafted with grafted talc. The formation of ester group peak in talc-g-PMMA spectrum has proven that the presence of PMMA onto the talc surface.